Peunerovská odyssea. Problematika měšťanské konverze na pozadí osudů raně novověké těšínské rodiny - Veronika Chmelařová (Theatrum Historiae)
The article focuses on the topic of conversion which represents a specific part of the process of the recatholization in urban society. It follows the topic in the context of the Silesian town of Teschen in the second half of the 17th century. In this period Habsburgs succeeded to Teschen´s princely throne and initiated various steps to restore the original position of the Catholic faith and the church in the area. Some of them affected also the central person of this article, local urban scrivener Timotej Peuner. Timotej, as well as the other protestant members of the town council, was forced to convert to Catholicism. The article describes tools of the recatholization by following his life story. The recatholization is perceived here as a part of a wider process of communication. The paper studies participants of the recatholization which became strongly individualised. Going through the urban and the church sources the article reveals structure of local social, economical and religious network connected to Timotej Peuner. Therefore it reveals more of the social and religious background of the conversion and describes its influence on Peuner´s close family and wider Teschen’s society.